Influence of Social Support on Teachers' Attitudes Toward Inclusive Education - Desombre, Caroline; Delaval, Marine; Jury, Mickaël (Frontiers in Psychology, 2021)
Inclusive education is at the heart of educational policy world-wide. Teachers' attitudes toward inclusive education, which are often associated with the success of the policy, have been studied extensively. Various factors related to teachers, students with special educational needs (SEN) and different specific contexts have been identified. In the current study, we explored the influence of social support on teachers' attitudes toward inclusive education. In a pilot study implying teachers, we replicated, in the French context, previous results showing a correlational link between social support and attitudes toward inclusion. Specifically, we showed that the more social support they perceived with regard to their attempts to include students with SEN, the more positive the teachers’ attitudes toward inclusive education. In an experiment involving 314 teachers we then explored the causal link between these variables. Results showed that highlighting the support teachers receive improves their attitudes in comparison with highlighting a lack of support or a control condition in which support is not mentioned. These studies show the importance of supporting inclusive education in the schools. This support can be provided in different ways (emotional, informational, instrumental, etc.) and by different actors (colleagues, supervisors).